2021
DOI: 10.1051/0004-6361/202141444
|View full text |Cite
|
Sign up to set email alerts
|

Large gaps and high accretion rates in photoevaporative transition disks with a dead zone

Abstract: Context. Observations of young stars hosting transition disks show that several of them have high accretion rates, despite their disks presenting extended cavities in their dust component. This represents a challenge for theoretical models, which struggle to reproduce both features simultaneously. Aims. We aim to explore if a disk evolution model, including a dead zone and disk dispersal by X-ray photoevaporation, can explain the high accretion rates and large gaps (or cavities) measured in transition disks. M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 129 publications
1
35
0
Order By: Relevance
“…However, the latter study was entirely based on SED based transition disk candidates rather than confirmed cavities from millimeter continuum imaging. Furthermore, several studies with more advanced photoevaporation models have shown that larger cavity sizes with higher accretion rates could be produced as well with photoevaporative clearing (Ercolano et al 2018;Picogna et al 2019;Gárate et al 2021). The new Lupus transition disk sample allows a comparison over a large range of cavity sizes and the latest photoevaporation models.…”
Section: Origin Of Small Cavitiesmentioning
confidence: 96%
See 4 more Smart Citations
“…However, the latter study was entirely based on SED based transition disk candidates rather than confirmed cavities from millimeter continuum imaging. Furthermore, several studies with more advanced photoevaporation models have shown that larger cavity sizes with higher accretion rates could be produced as well with photoevaporative clearing (Ercolano et al 2018;Picogna et al 2019;Gárate et al 2021). The new Lupus transition disk sample allows a comparison over a large range of cavity sizes and the latest photoevaporation models.…”
Section: Origin Of Small Cavitiesmentioning
confidence: 96%
“…The disks without resolvable inner cavity are included as upper limits based on the analysis in Section 5.1. The photoevaporation regimes from a number of modeling studies (Owen et al 2011;Ercolano et al 2018;Picogna et al 2019;Gárate et al 2021) overlaid. These are the regimes with a >0.1% probability of finding a disk with the given cavity and accretion rate as the result of X-ray photoevaporation for different assumptions.…”
Section: Origin Of Small Cavitiesmentioning
confidence: 99%
See 3 more Smart Citations